2018
DOI: 10.1016/j.cub.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Host Energy Source Is Important for Disease Tolerance to Malaria

Abstract: Pathologic infections are accompanied by a collection of short-term behavioral perturbations collectively termed sickness behaviors [1, 2]. These include changes in body temperature, reduced eating and drinking, and lethargy and mimic behaviors of animals in torpor and hibernation [1, 3-6]. Sickness behaviors are important, pathogen-specific components of the host response to infection [1, 3, 7-9]. In particular, host anorexia has been shown to be beneficial or detrimental depending on the infection [7, 8]. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 39 publications
9
74
0
Order By: Relevance
“…2). These findings are consistent with recent studies utilizing the P. chabaudi AJ model, where 2DG was likely exacerbating the damaging effects of severe anemia (25). We thus asked if the addition of the antimalarial antibiotherapy chloroquine would be sufficient to provide long-term survival (Fig.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…2). These findings are consistent with recent studies utilizing the P. chabaudi AJ model, where 2DG was likely exacerbating the damaging effects of severe anemia (25). We thus asked if the addition of the antimalarial antibiotherapy chloroquine would be sufficient to provide long-term survival (Fig.…”
Section: Resultssupporting
confidence: 88%
“…In our experiments, 2DG was sufficient to rescue mice from cerebral malaria, but they ultimately succumbed to fatal anemia in the absence of pathogen clearance. Our findings are consistent with those of Cumnock et al (25), who showed that 2DG may be detrimental in severe anemia. Indeed, we were able to rescue 2DG-treated animals that survived cerebral malaria by subsequent treatment with chloroquine, suggesting that any therapeutic use of 2DG for treating cerebral malaria will need to be combined with chemotherapeutic drugs targeting the parasite and that the use of 2DG must be carefully timed to the stage of the disease.…”
Section: Malarial Infection Induces Loss Of Appetite In Mice and Humanssupporting
confidence: 94%
See 1 more Smart Citation
“…We have previously shown that while administration of 2-DG to animals challenged with Poly I:C or influenza resulted in driving the unfolded protein response toward neuronal cell death leading to enhanced mortality, administration of 2-DG to animals challenged with LPS or Listeria resulted in enhanced survival by mechanisms which are yet to be fully identified but independent of the magnitude of the inflammatory response (12). We have also recently shown using mouse models of malaria that 2-DG protected animals from cerebral malaria by affecting hemostasis while others have shown that it potentiates mortality in malarial models of fatal anemia (57,58). It is likely that the composite outcome of 2-DG depends on the given set of biological processes that require glucose in any particular organismal state.…”
Section: Discussionmentioning
confidence: 99%
“…In a new study in this issue of Current Biology, Cumnock et al [6] find that mice infected with malaria experience a range of sickness behaviours including anorexia, lethargy and hypothermia. By explicitly testing the link between behavioural and metabolic outputs during the entire infection cycle, the authors showed that these symptoms could be relieved with a relatively simple and cheap treatment that improves glycolysis in severely anaemic mice, making them more tolerant to malaria.…”
mentioning
confidence: 99%